2012
DOI: 10.1080/01904167.2012.689914
|View full text |Cite
|
Sign up to set email alerts
|

15NITROGEN STUDY ON ABSORPTION, DISTRIBUTION AND UTILIZATION OF NITROGEN APPLIED IN EARLY SUMMER IN RED FUJI APPLE

Abstract: 2 Total nitrogen (N) concentration (N%), N derived from 15 N-fertilizer (Ndff%), amount of 15 N uptake (ANU) in main organs (leaves, shoots, roots, fruits), and N use efficiency (NUE) were measured to assess N absorption, distribution, and utilization of Red Fuji apple trees across two years using a 15 N-enriched urea method. The N% in leaves and fruits decreased while those in shoots and roots increased in both years. The Ndff% and ANU in roots were highest at fruitlet stage than those in leaves, shoots and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
3
5
0
Order By: Relevance
“…For an apple tree, it has been shown that nitrogen distribution to support the growth of individual fruits and shoots is directly related to the distribution of assimilates in the plant [5]; therefore, one should expect differences in nitrogen uptake by trees in years with unequal fruit load. In our experiment, apple productivity in 2018 was 4.5 times higher than in 2019.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For an apple tree, it has been shown that nitrogen distribution to support the growth of individual fruits and shoots is directly related to the distribution of assimilates in the plant [5]; therefore, one should expect differences in nitrogen uptake by trees in years with unequal fruit load. In our experiment, apple productivity in 2018 was 4.5 times higher than in 2019.…”
Section: Resultsmentioning
confidence: 99%
“…For fruit trees, especially in the first years after planting, the nitrogen utilization rate is quite low and amounts to 15 ... 33% [4,5]. For this reason, some fruit growers believe they should apply an amount of nitrogen much higher than the remove of the element with the crop [3].…”
Section: Introductionmentioning
confidence: 99%
“…Applied N can be traced throughout the tree through the use of an N source enriched with the stable isotope 15 N (Hauck and Bremner, 1976;Dong et al, 2002). This approach has been used to quantify fertilizer N uptake in deciduous fruit tree crops, including apples (Neilsen et al, 1997;Guak et al, 2003;Zhang et al, 2012), pears (Quartieri et al, 2002), cherries (San-Martino et al, 2010;Rivera et al, 2016), and evergreen fruit tree crops, such as citrus (Martínez-Alcántara et al, 2011). For example, when 10-year-old field-grown apple trees were supplied with 15 N-labeled fertilizer at bud burst and destructively sampled periodically, the NUpE of 9.9 to 12.2% was quantified over two seasons and the majority of NDF was allocated to perennial organs (Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been used to quantify fertilizer N uptake in deciduous fruit tree crops, including apples (Neilsen et al, 1997;Guak et al, 2003;Zhang et al, 2012), pears (Quartieri et al, 2002), cherries (San-Martino et al, 2010;Rivera et al, 2016), and evergreen fruit tree crops, such as citrus (Martínez-Alcántara et al, 2011). For example, when 10-year-old field-grown apple trees were supplied with 15 N-labeled fertilizer at bud burst and destructively sampled periodically, the NUpE of 9.9 to 12.2% was quantified over two seasons and the majority of NDF was allocated to perennial organs (Zhang et al, 2012). A similar approach, with the inclusion of successive xylem sap sampling, was deployed on 2-year-old apple trees (Guak et al, 2003) demonstrating that leaf growth was mostly supported by remobilized N, and root uptake did not commence until 14 days after remobilization had begun.…”
Section: Introductionmentioning
confidence: 99%
“…Part of the N absorbed by roots is preferably transported to growing organs such as leaves, annual shoots and fruits (El-Jendoubi et al, 2013;Jordan, 2015). Moreover, part of the N accumulated in annual organs is redistributed, after harvesting, to storage organs such as stem, shoots older than one year and, mainly to the roots (Rivera et al, 2016;Zhang et al, 2012). If large amounts of N from the fertilizer accumulate inside peach trees in the fertilizer application year, it may not be necessary applying large N rates to the soil in the next crop to reduce soil dependence on the fertilizer (Jordan et al, 2012) or even on N, since this element often derives from organic matter mineralization and the decomposition of plant residues (Sabahi et al, 2016;TerAvest et al, 2010).…”
mentioning
confidence: 99%